PENGGUNAAN AYAT-AYAT AL-QUR’AN SEBAGAI MENTRE DALAM TRADISI MASYARAKAT SASAK - Hayuni Malia (university Of islam, 2023)
The phenomenon of using the verses of the Qur’an as a mentre (mantra) in the traditions of the Sasak people is still developing today. However, the fact is that in several ways there is a discrepancy between the meaning of the Qur'anic verses used and its intended function. These verses are used as mentre only because they have the same homophone (sound) with the Sasak dialect or language. This study aimed to reveal how the reception of the Sasak people to the use of verses of the Qur’an as a mentre in which has phonological similarities (homophones) with Sasak vocabulary or dialect. The research data was taken from interviews with several community leaders in Darmaji village, Kopang sub-district, Central Lombok who had in-depth knowledge of ministers. This study used a qualitative method with a phenomenological approach as an analytical tool. The results of the study showed that the use of inconsistent verses of the Qur’an (meanings and functions did not match) was a form of the Sasak people's belief in the power of the Qur’an. In addition, the incompatibility in the meaning of the Qur'an which was adapted based on the sound similarity with the Sasak dialect was a form of creativity of the Sasak people in interpreting the Qur'an. In line with that, the authors conclude that the phenomenon that occurs in the mentre tradition of the Sasak people is a form of community of the Qur’an in a magical space.